Berberine Promotes OATP1B1 Expression and Rosuvastatin Uptake by Inducing Nuclear Translocation of FXR and LXRα - Liu, Mingyi; Zhu, Dandan; Wen, Jinhua; Ding, Wei; Huang, Shibo; Xia, Chunhua; Zhang, Hong; Xiong, Yuqing (Frontiers in Pharmacology, 2020)
Berberine, a quinoline alkaloid, can be used in combination with statins to enhance hypolipidemic effects and reduce the dose and side effects of statins. The hypolipidemic effects of statins in the liver are mainly regulated by OATPs (Organic anion transporting polypeptides), and the expression of OATPs is regulated by nuclear receptors. Berberine has been reported to affect nuclear receptors. However, whether berberine affects the uptake of statins by regulating nuclear receptor-mediated expression of OATPs remains to be determined. The aim of this study was to investigate the effects of berberine on the expression of OATP1B1 in HepG2 and explore the underlying mechanism. In HepG2 cells, 10-50 μM berberine significantly increased the uptake of rosuvastatin by inducing the expression of OATP1B1 mRNA and protein. Dual-Luciferase reporter assay showed that luciferase activity of hFXR and hLXRα activated OATP1B1 promoter was increased by 2.5-50 μM berberine in a dose-dependent manner, with half-maximal effective concentration (EC50) of 12.19±0.86 μM and 32.15±2.32 μM, respectively. In addition, after silencing FXR or LXRα by siRNA, berberine-induced OATP1B1 expression was significantly attenuated. Western blot analysis of FXR and LXRα protein levels in the cytoplasm and nucleus of HepG2 cells after treatment with berberine showed that berberine induced nuclear translocation and activation of FXR and LXRα. In conclusion, berberine-induced nuclear translocation of FXR and LXRα could activate OATP1B1 promoter, resulting in enhanced expression of OATP1B1 and increased uptake of statins.